Randomised comparison of three methods of administering a screening questionnaire to elderly people: findings from the MRC trial of the assessment and management of older people in the community. Issue 7326 (15th December 2001) - Smeeth, Liam; Fletcher, Astrid E; Stirling, Susan; Nunes, Maria; Breeze, Elizabeth; Ng, Edmond; Bulpitt, Christopher J; Jones, Dee
Abstract: Objective: To compare three different methods of administering a brief screening questionnaire to elderly people: post, interview by lay interviewer, and interview by nurse. Design: Randomised comparison of methods within a cluster randomised trial. Setting: 106 general practices in the United Kingdom. Participants: 32 990 people aged 75 years or over registered with participating practices. Main outcome measures: Response rates, proportion of missing values, prevalence of self reported morbidity, and sensitivity and specificity of self reported measures by method of administration of questionnaire for four domains. Results: The response rate was higher for the postal questionnaire than for the two interview methods combined (83.5% v 74.9%; difference 8.5%, 95% confidence interval 4.4% to 12.7%, P<0.001). The proportion of missing or invalid responses was low overall (mean 2.1%) but was greater for the postal method than for the interview methods combined (4.1% v 0.9%; difference 3.2%, 2.7% to 3.6%, P<0.001). With a few exceptions, levels of self reported morbidity were lower in the interview groups, particularly for interviews by nurses. The sensitivity of the self reported measures was lower in the nurse interview group for three out of four domains, but 95% confidence intervals for the estimates overlapped. Specificity of the self reported measures varied little by method of administration. Conclusions: Postal questionnaires were associated with higher response rates but also higher proportions of missing values than were interview methods. Lower estimates of self reported morbidity were obtained with the nurse interview method and to a lesser extent with the lay interview method than with postal questionnaires.